2015
DOI: 10.3390/molecules201219738
|View full text |Cite
|
Sign up to set email alerts
|

Pyranocoumarins from Root Extracts of Peucedanum praeruptorum Dunn with Multidrug Resistance Reversal and Anti-Inflammatory Activities

Abstract: Abstract:In the search for novel herbal-based anticancer agents, we isolated a new angular-type pyranocoumarin, (+)-cis-(3 1 S,4 1 S)-3 1 -angeloyl-4 1 -tigloylkhellactone (1) along with 12 pyranocoumarins (2-13), two furanocoumarins (14, 15), and a polyacetylene (16) were isolated from the roots of Peucedanum praeruptorum using chromatographic separation methods. The structures of the compounds were determined using spectroscopic analysis with nuclear magnetic resonance (NMR) and high-resolution-electrospray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Several reports including our previous study identified that the seeds of D. sophia contained several cytotoxic and anti-inflammatory substances to induce the death of various cancer cell lines in vitro [1921]. We also showed that pyranocoumarins from P. praeruptorum possessed considerably significant multidrug-resistant reversal activity in multidrug resistant MES-SA/Dx5 cancer cells [22]. A. japonica as well contained anti-proliferative and pro-apoptotic compounds that kill some cancer cells such as human leukemia and prostate cancer [23, 24].…”
Section: Introductionmentioning
confidence: 76%
“…Several reports including our previous study identified that the seeds of D. sophia contained several cytotoxic and anti-inflammatory substances to induce the death of various cancer cell lines in vitro [1921]. We also showed that pyranocoumarins from P. praeruptorum possessed considerably significant multidrug-resistant reversal activity in multidrug resistant MES-SA/Dx5 cancer cells [22]. A. japonica as well contained anti-proliferative and pro-apoptotic compounds that kill some cancer cells such as human leukemia and prostate cancer [23, 24].…”
Section: Introductionmentioning
confidence: 76%
“…SKD, which is isolated from the fruit of Lomatium suksdorfii, and its derivatives are notable because of their inhibitory activities against the replication of human immunodeficiency virus (HIV) Xie, Takeuchi, Cosentino, & Lee, 1999). Lee et al recently reported regarding the anti-inflammatory activities of PTX and SKD isolated from the roots of P. praeruptorum (Lee et al, 2015). We here evaluated and compared the anti-obesity effects of the dihydropyranocoumarins of PJT using differentiated 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of pyranocoumarins, which are structurally analogous to PTX, possessed similar bioactivities but different potencies (Chen et al, 2008;Lee, Lee, Kim, & Bang, 2015;Thastrup et al, 1983). Although Choi et al recently reported the anti-adipogenic and anti-diabetic effects of cis-3 0 ,4 0 -diisovalerylkhellactone (cDIVK, PubChem CID: 44584701) isolated from PJT (Choi et al, 2016), only a few studies has reported the anti-obesity effects of any coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enantiomers and diastereomers could occur (Sarkhail 2014). Angular dihydropyranocoumarins were isolated mainly from the genera Peucedanum, Angelica, and Seseli, which belong to the Umbelliferae family (Lee et al 2015;Chun et al 2016;Jung et al 2012). It was reported that the khellactone esters showed antiinflammatory effect (Yu et al 2012), antibacterial activity (Lu et al 2001), tracheal relaxant activity (Zhao et al 1999), monoamine oxidase inhibitory activity (Huong et al 1999), antiplatelet aggregation activity (Jong et al 1992), and anti-tumor activity (Duh et al 1991).…”
Section: Peucedanum Japonicum Thunberg Is Widely Distributed In Southmentioning
confidence: 99%